O PIBID na escola: a visão dos sujeitos sociais a respeito de suas práticas educacionais vivenciadas através do Programa Institucional de Bolsas de Iniciação à Docência (PIBID) - Araújo, Vanessa Gomes de (2016)
The Institutional Program of Initiation to Teaching, known as PIBID, is a Brazilian national public policy under the responsibility of the Ministry of education, through CAPES, an official agency, which gives priority to the elevation of the quality level of basic education, promoting the integration of university students in the everyday life of public schools. With expertise in high schools, the PIBID is, not only, thought of as a tool for teacher training, but also as an active agent in the process of teaching- learning. This dissertation, proposed through the Post Graduate Program - “Master's degree in Sociology” - from ‘Universidade Federal do Ceará (UFC)”, has as objective the critical reflection on the construction of everyday relations involving the above-mentioned Program, which is focused on two local high schools: “Liceu do Ceará” and “Liceu do Conjunto Ceará”. It is also to consider that this project, while institutional action, also aims to create new teaching practices in basic education. With the PIBID deployment in schools, it is interesting to think about the relationships that are established between coordinators of sub-projects, graduating students, teachers, supervisors, high school students and the other members of the school, since the school is also a field where power relations and, moreover, the influence of these relationships in the construction of knowledge happens. It is also important to think over how the social actors involved in the program are part of the knowledge, which is fragmented in school culture, providing that to build and engage an interdisciplinary practice it is necessary to establish a dialogue between all the actors involved in the teaching-learning process.